Integração ensino e serviço em hospital universitário: a percepção do discente em enfermagem - Tenório, Giselle Mamede (2014)
In recent decades the formation of argumentative, reflective and health social needs caring nurses has frequently been pursuit. The National Curriculum Guidelines (2001) provide guidance on the curriculum of nursing course in the country. Among these guidelines, it is highlighted the integration between the educational institution and the institutions that provide health care to the community and which are the practice field during the supervised internships, which occur on the last year of the course. This research proposed to understand the perceptions of nursing students on the integration between teaching and service during the nursing degree internships at University Hospital. It was delineated a case study using qualitative approach, with nine students of the last period of nursing course as subjects. The data were built by conducting a focus group and analyzed using content analysis technique according to Bardin (2011), emerging six categories to be analyzed: planning ( activities ) ; supervision; importance of supervised internship; reception at university hospital; posture of the nursing professional and positive and negative features of supervised internships. The survey results point to a positive teaching and service integration in the perception of students. It was observed, however, discordant points between themselves and in relation to what the national curriculum guidelines and relevant studies say, leading us to propose that this points need to be adjusted so that they can contribute to the formation of better professionals in the area.